THE USE OF WORD ORDER STRATEGIES IN TEACHING SARF, ESPECIALLY IN THE TOPIC OF PATTERNS, FOR SECOND-GRADE STUDENTS AT DAR AL-UKHUWAH GIRLS’ INSTITUTE 2 - Faricha Nidaul Hanifa; Muassomah Muassomah; Jehan Salsabila (Universitas Islam Negeri Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2023)
The learning of Shorof or morphology is sometimes considered easy for beginners in the Arabic language, so this subject is now taught in 2nd-grade junior high school in various schools, including at Pondok Pesantren Daarul Ukhuwwah Putri 2 Malang. This research discusses the learning strategies of Shorof using a word arrangement game adapted to the curriculum and teaching materials of the pondok, namely the KMI curriculum. The researcher aims to describe the process of learning Shorof with the word arrangement strategy on the material of Shorf Sighatul Kalimat for 2nd-grade female students at Pondok Pesantren Daarul Ukhuwwah Putri 2 and to describe the strengths and weaknesses of this strategy. This research method employs qualitative descriptive research. Data obtained includes field notes, photos, documentation, and others. Qualitative research is conducted based on qualitative paradigms, strategies, and model implementations. The results of the discussion can be concluded that the use of the Word Arrangement Strategy in the learning of Shorf Sighatul Kalimat for 2nd-grade female students at Pondok Pesantren Daarul Ukhuwwah Putri 2 has a positive impact on Shorof learning. This is evident from the observation results showing an increase in the enthusiasm of female students in learning and providing new innovations for teachers in delivering materials and assessments.